Sorption of PCBs to environmental plastic pollution in the North Atlantic Ocean:Importance of size and polymer type - Syberg, Kristian; Knudsen, Camilla M.H.; Tairova, Zhanna; Khan, Farhan R.; Shashoua, Yvonne; Geertz, Torsten; Pedersen, Henrik B; Sick, Claudia; Mortensen, John; Strand, Jakob; Palmqvist, Annemette (Case Studies in Chemical and Environmental Engineering, 2020)
Plastic pollution is a great threat to the marine environment. Owing to its low density, a substantial fraction of plastic debris is transported across ocean surfaces by currents. Consequently, plastic debris has been concentrated in oceanic gyres such as the North Atlantic subtropical Gyre (NASG). This study presents data that describes plastic abundances and the concentrations of adhered PCBs (polychlorinated biphenyls) from 15 surface trawls conducted within and outside the NASG. Abundance of plastic pieces was significantly higher inside the gyre than outside supporting earlier findings about the importance of the gyres as accumulation zones for plastic debris. Concentrations of PCBs were comparable among different sizes fractions when measured per plastic piece but significantly higher on smaller pieces when measured per weight unit. Polyethylene pieces furthermore had higher concentrations of PCB than polypropylene pieces. These findings highlight the importance of accounting for particle size and polymer type when assessing sorbed contaminants to environmental plastic pollution.